Comparison of Radiologic and Pathological Diagnosis in Patients Presenting with Bloody Nipple Discharge - Zaman, Sajid; Shah, Maham; Naqvi, Rifaat Qamar; Abbasi, Muhammad Sheraz; Khalil, Khurram Khan; Noor, Asad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess efficacy of ultrasound in detecting breast carcinoma in patients with abnormal nipple discharge, given the limitations of mammography in this context. Study Design: Prospective observational study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Jul 2023 to Mar 2024. Methodology: The study included 139 female patients with abnormal nipple discharge who underwent traditional breast ultrasound followed by histopathological confirmation through biopsy. Results: The demographic data revealed a majority in the 46-66 age group (62.59%) and a longer disease duration exceeding 6 months (73.39%). Ultrasonography demonstrated significant diagnostic accuracy, identifying 89 out of 93 positive cases as true positives and correctly identifying 36 out of 46 negative cases as true negatives, with a sensitivity of 95.7%. However, it also showed 10 false positives, leading to an accuracy of 78.3%. Conclusions: The study highlights the efficacy of ultrasound in differentiating between benign and malignant breast lesions linked to abnormal nipple discharge, demonstrating significant diagnostic accuracy. Despite concerns about false positives, ultrasound remains a valuable non-invasive diagnostic tool, contributing to improved clinical decision-making and patient comfort.